2010
DOI: 10.1017/s0142716410000068
|View full text |Cite
|
Sign up to set email alerts
|

The linguistic correlates of conversational deception: Comparing natural language processing technologies

Abstract: The words people use and the way they use them can reveal a great deal about their mental states when they attempt to deceive. The challenge for researchers is how to reliably distinguish the linguistic features that characterize these hidden states. In this study, we use a natural language processing tool called Coh-Metrix to evaluate deceptive and truthful conversations that occur within a context of computer-mediated communication. Coh-Metrix is unique in that it tracks linguistic features based on cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
2
7

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 42 publications
2
39
2
7
Order By: Relevance
“…Bond and Lee () demonstrated that truthful statements of incarcerated prisoners included more sensory and perceptual processes when they told the truth compared to when they lied. Other studies have reported similar results (Duran, Hall, McCarthy, & McNamara, ; Hancock, Curry, Goorha, & Woodworth, ; Schelleman‐Offermans & Merckelbach, ; Toma & Hancock, ; Vrij, Mann, Kristen, & Fisher, ). To be sure, findings have not always been consistent; two studies reported negative findings on words related to complexity and pronoun use (Hancock et al ., ; Toma & Hancock, ).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Bond and Lee () demonstrated that truthful statements of incarcerated prisoners included more sensory and perceptual processes when they told the truth compared to when they lied. Other studies have reported similar results (Duran, Hall, McCarthy, & McNamara, ; Hancock, Curry, Goorha, & Woodworth, ; Schelleman‐Offermans & Merckelbach, ; Toma & Hancock, ; Vrij, Mann, Kristen, & Fisher, ). To be sure, findings have not always been consistent; two studies reported negative findings on words related to complexity and pronoun use (Hancock et al ., ; Toma & Hancock, ).…”
supporting
confidence: 62%
“…One source of indicators is verbal and comes from analyses of words used to provide statements and answer questions. Lies contain fewer words and omissions of information; are less plausible, structured and logical; are more internally discrepant and ambivalent; contain repeated details and lack contextual embedding; and include more descriptions of what did not occur (DePaulo et al ., ; Duran, Hall, McCarthy, & McNamara, ; Newman, Pennebaker, Berry, & Richards, ; Porter, Birt, Yuille, & Lehman, ; Porter & ten Brinke, ; Vrij, ).…”
mentioning
confidence: 99%
“…However, this does not preclude any possible differences between truth tellers' and liars' recollections. Script generation from imagined events is likely to be different, because mental representations of false events are likely to be less coherent than those of truthful events (Duran, Hall, McCarthy, & McNamara, ). We examined the frequency of temporal connectives in responses to a reverse order question, and a distinction was made between normal (‘and then’) and reverse order (‘before that’) connectives.…”
Section: The Effect Of the Second Interviewermentioning
confidence: 99%
“…The use of linguistic cues to indicate potentially deceptive communications has also been studied in a variety of modalities and contexts (e.g., [24,13,7]). While text-based deception in computer mediated communication is a specific area of study [29,30,3], there has been less of a concentration on the various types of deception strategies that individuals utilize in their duplicitous communications, especially as people more often use informal, succinct messages as a result of the widespread adoption of social media.…”
Section: Introductionmentioning
confidence: 99%